ANALYZING THE IMPACT OF TRAINING DESIGN ON EMPLOYEE PERFORMANCE: A GENDER AND AGE-BASED STUDY (International Journal of Food and Nutritional Sciences, 2023)
This research paper examines the intricate relationship between training design and employeeperformance, with a particular emphasis on how this relationship is influenced by gender andage. Utilizing descriptive statistics and independent sample t-tests, the study analyzes data froma diverse group of employees across various industries.